PENGARUH PENAMBAHAN STARTER YOGURT DAN SUSU SKIM TERHADAP KUALITAS YOGURT SUSU KACANG HIJAU (Vigna radiata L) - Aryati Rambu Nalu; Kukuk Yudiono; Sri Susilowati (BiSTeK Pertanian, 2019)
Yogurt is a type of beverage classified as a refreshment drink which is produced through a fermentation process that uses Lactic Acid Bacteria. Most legumes have been widely used as raw materials in the making of a milk known as vegetable milk. Legume milk contains amino acids that are almost equivalent to the amino acid content of animal milk so it can be used as a base substitute material for fermented animal milk. Processed green bean milk yogurt is a form of food diversification. Skim milk is a lowfat milk added in the production of green bean milk yogurt, and yogurt starter is an important factor in the process of yogurt making. The purpose of the study is to determine the effects of the addition of yogurt starter and skim milk on the quality of green bean milk. The research design is 2-Factor Factorial Design arranged with Completely Randomized Design (CRD). Factor I consists of 2 levels, namely 12 grams of skim milk and 15 grams of skim milk; factor II consists of 3 levels, namely 15 ml, 20 ml, and 25 ml of starters. Observation variables consist of pH, total acid, viscosity, protein content, lactic acid bacteria, organoleptic aroma test, organoleptic texture test, and organoleptic taste test. From the results of this study, the highest results obtained in the treatment consist of: a) 12 grams of skim milk and 25 ml of 8.13%,Total Acid, Organoleptic Aroma Test 4.57, Organoleptic Texture Test 4.73; b) 15 grams of skim milk and 25 ml of starter of pH 4.17, Viscosity 8.67 cP, protein content 0.94%, Lactic Acid Bacteria 2933.33 x 103 CFU / mL, Organoleptic Aroma Test 4.57, Organoleptic Texture Test 4.61, Organoleptic Taste Test 5.02.